Pathomorphological and immunohistochemical characteristics of the testicle in children with critical ischemia during acute torsion - Volos, L.I.; Gorbatyuk, O.M.; Veselyi, M.Yu.; Veselyy, S.V.; Lavrov, D.V. (Морфологія / Morphologia / Morfologìâ, 2024)
Background. The occurrence of acute torsion of the testicle in children leads to ischemia of the testicle, and in the absence of timely medical assistance - to the loss of the organ. The period from 12 hours to 24 hours from the onset of the disease leaves only a 20% chance of saving the genital gonad. There are still no exact signs of viability of the affected gonad in case of critical ischemia of the testicle due to its torsion. Therefore, the study of the dynamics of changes in morphological structures in the course of acute testicular torsion, morphological and functional disorders resulting from torsion, is of great practical interest, because there is no consensus on the nature and degree of these changes in the affected gonad. Objective: study of the nature and severity of pathomorphological changes and immunohistochemical features of the acute torsion testicle in children within 12.1-24 hours or more from the onset of the disease. Methods. A histological, histochemical, and immunohistochemical study of testicular tissue biopsies taken during the operation of detorsion and orchiopexy, and orchidectomy within 12.1–24 hours or more from the onset of clinical symptoms of acute unilateral torsion in 16 patients was conducted. Results. The morphological study of the gonads showed that the duration of acute torsion of 12.1–24 hours or more is characterized by severe pathological changes found in the testicles. After 18 hours of acute ischemia, tubules were visualized in many fields of view in the form of shadows with the impossibility of identifying the structures due to hemorrhagic or ischemic infarcts. Immunohistochemical typing demonstrated the absence of expression of vimentin and calretinin, which indicated the death of sustentocytes (Sertoli cells) and Leydig cells. With a duration of acute torsion of 12.1-18 hours, a histochemical study of glycogen in the cytoplasm of spermatogonia, spermatocytes, and sustentocytes using the PAS-reaction showed that some cells of the spermatogenic epithelium were characterized by irreversible changes preceding necrosis, although giant multinucleated spermatids with relatively preserved glycogen, which meant there was a minimal chance for saving the gonad. Conclusion. Total duration of symptoms and degree of male gonadal torsion are the main prognostic factors for testicular preservation or necrosis in episodes of torsion. The duration of an acute torsion of 12.1-18 hours, according to morphological research, leaves in 42,9% of cases the presence of a minimal chance of saving the genital gonad. After 18 hours from the onset of acute complete testicular torsion in children, the operation of choice is orchidectomy.